Factors Influencing Cloud Computing in Telecommunications Companies - Raed Wishah; Marwan Al-Nsour; Malek Alharafsheh; Saleh AlKhalaileh; Farah Alshbeekat (Institute of Advanced Engineering and Science, 2018)
This study aims to identify the role of cloud computing in achieving success in e-governance in Jordan. This paper investigates the effect of four accomplishment aspects (availability, flexibility, cost saving and scalability) for executing cloud computing technology in telecommunication companies on Jordan e-governance implementation. A questionnaire was developed to collect data from respondents working for the three-main public mobile telephone network operators: Zain, Orange and Umniah. The Statistical Package for Social Sciences program was used in the descriptive analysis of the responses. The results show that all four success factors have a high level of impact, separately and together, on e-governance in Jordan. Cost saving has the highest impact, followed by scalability, availability and flexibility. Based on these results, the study makes some suggestions for further research that could enrich understanding of the implementation of cloud computing and its effect on egovernance in Jordan.